STRATEGIC LEADERSHIP OF CITIZEN SECURITY IN THE CALLAO REGION AND ITS RELATIONSHIP WITH NATIONAL SECURITY, PERIOD 2017-2018 - Bolaños Maaldonado, Miguel Angel (2021)
"Strategic Leadership of Citizen Security in the Callao Region and National Security, period 2017-2018" has as its main objective, to determine whether the strategic Leadership of Citizen Security in the Callao Region is related to National Security, period 2017-2018. The study methodologically belongs to a quantitative approach, with a descriptive correlational scope and a non-experimental research design, with a study population consisting of officials with strategic responsibility in Citizen Security in the fight against Common Crime in the Cercado del Callao, such as political and police authorities, totaling 129 people and a sample of 97 people, using a Likert-type questionnaire, and the use of the Chi-Square test for the demonstration of the Hypotheses. During the development of the present research, the following general conclusion is reached: that the strategic Leadership of Citizen Security in the Callao region is positively related to National Security, period 2017-2018. As a final part of the study, the recommendations that have been reached are exposed, based on them, the proposal for the implementation of strategies to optimize the strategic Leadership of Citizen Security in the Callao region has been formulated.